Estimation of open & short circuit fault detected distance in the underground transmission cable using Arduino & GSM module - Rahman, Md. Rashidur; Ullah, Md. Arafat; Sakib, Nazmul Hasan; Arnab, Johaor Kowsar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.